Shifts in the partitioning of benthic and pelagic primary production within and across summers in Lake Mývatn, Iceland. Issue 1 (2nd January 2021) - McCormick, Amanda R.; Phillips, Joseph S.; Botsch, Jamieson C.; Ives, Anthony R.
ABSTRACT: The relative contributions of benthic and pelagic primary production affect ecosystem function, but studies documenting natural variation in the partitioning of production (i.e., autotrophic structure) are uncommon. This study examines autotrophic structure of shallow Lake Mývatn over 7 summers (2012–2018). We used routine measurements of benthic gross primary production (GPP), pelagic chlorophyll a concentrations, and pelagic production to estimate benthic and pelagic maximum productivity ( P max ) across summers. With these parameters and corresponding incident light and water clarity data, we estimated in situ benthic and pelagic GPP. Our results demonstrated substantial variation in Mývatn's autotrophic structure within and across summers. Benthic GPP often exceeded pelagic GPP. However, periods of increased phytoplankton abundance were associated with increased light attenuation and, consequently, declines in benthic GPP. These effects were strongest in 3 summers with dense cyanobacteria blooms, in which the benthic fraction of total production declined from >95% to <20%. Reduced light levels over a 2-week period were associated with low benthic P max, implying that past shading by phytoplankton may decrease the photosynthetic potential of benthic producers. Moreover, variation in estimated benthic P max values can affect the point at which autotrophic structure shifts toward pelagic-dominated conditions. Overall, our study demonstrates that the balance between benthic and pelagic production can vary greatly at intra- and interannual scales because of changes in the photosynthetic capacity of both pelagic and benthic primary producers. Understanding natural variation in lake autotrophic structure may inform how benthic and pelagic production respond to ongoing and future environmental changes.